Cognitive profile in CADASIL. Issue 2 (17th January 2006) - Buffon, F; Porcher, R; Hernandez, K; Kurtz, A; Pointeau, S; Vahedi, K; Bousser, M-G; Chabriat, H
Abstract : Background: The spectrum of cognitive alterations associated with CADASIL, a model of pure vascular dementia, has not been thoroughly evaluated. Objectives: The aims of this study were: (i) to describe the cognitive profile in CADASIL patients according to age; (ii) to compare the profile of patients with dementia with that of patients without dementia; and (iii) to determine the association between alterations in performance in different cognitive domains. Methods: Forty two consecutive individuals with CADASIL (35–73 years old) were investigated. Cognitive skills were analysed in five domains (executive functions, reasoning, attention, memory, visuospatial abilities) according to age and compared between patients with and without dementia. Associations between cognitive performance and stroke were tested. Results: The youngest patients presented with attention (69%), memory (70%), and executive disturbances (100%). Visuospatial abilities and reasoning deteriorated with age, mainly after the age of 60. About one quarter of patients had dementia, and 75% of these were >60 years of age. Age >60 years was associated with a Rankin score >3 and a significant deficit in all cognitive domains. No association was found between dementia and the number of ischaemic attacks. Episodic memory disorder was characterised by difficulties in retrieval rather than impairment of the encoding process. Conclusion: Cognitive decline in CADASIL is dominated by early impairment of executive functions. Skills in other cognitive domains deteriorate with age and are found to be diffusely impaired in patients with dementia. The relative preservation of the encoding process in episodic memory impairment, even in individuals with dementia, is noteworthy.